Design of a Decision Support System for Test Ordering in General Practice: Choices and Decisions to Make - van Wijk, M.; Mosseveld, M.; van der Lei, J. (Methods of Information in Medicine, 1999)
The increased availability of tests in the past years has been accompanied by an increased number of blood tests ordered by general practitioners. Dutch investigators report a lack of general practitioners’ knowledge concerning the indications for blood tests leading to inappropriate and inadequate use of diagnostic tests. Taking advantage of the use of electronic patient records by Dutch general practitioners, the authors replaced the traditional paper forms for test ordering by a decision-support system. The objective of the decision-support system is to change test-ordering behavior. Designing a system to change test-ordering behavior, however, required the selection of a method to provide support. To study different methods for changing test-ordering behavior, the authors developed two versions of the decision-support system BloodLink. The first version, Blood-Link-Restricted, is based on the notion of restricting the number of choices presented to the general practitioners. The second version, BloodLink-Guideline, is based on the guidelines provided by the Dutch college of general practitioners.
Keywords: Decision Support; Guidelines; Test-ordering Behavior; General Practice